Designing a composition formulation of surface active substances for the pretreatment of knitted fabric - Skalozubova, Nataliia; Kunik, Aleksandra; Semeshko, Olga; Saribyekova, Yulia; Myasnykov, Sergey (Eastern-European Journal of Enterprise Technologies, 2016)
The process of pretreatment of knitted fabrics for dyeing is the most important technological operation. As a result of the pretreatment, fabrics acquire capability to wet evenly, which contributes to the uniform putting of the solutions of dyes and other decoration substances. Based on the analysis of the washing and wetting capacity of different classes of surface active substances, we determined those preparations, which ensure the optimal capillary properties of knitted fabric. A mathematical model by the wetting and washing capacities was obtained by the method of mathematical planning of the experiment – the Scheffe’s simplex lattice plan of the second order. Based on the obtained results, the Authors carried out optimization of the models “compositionproperty” and determined the optimal formulation of the composition for pretreatment of cotton knitted fabric for dyeing, g/l: SAS1=3,40; SAS2=2,75; SAS3=0,90; SAS4=2,90. It was found that the application of the proposed composition of SAS of the concentration 1,2 g/l for the technology of pretreatment of knitted fabric leads to a significant increase in the capillarity of knitted fabric (by 3 times) and the degree of fixation of active dye (by 7,5 %).